Position of “Land Information Letter” as Evidence of Land Ownership Rights in Land Registration Regulations - Clarisa Mutia Huda; Lego Karjoko; Isharyanto Isharyanto (Greenation International Journal of Law and Social Sciences, 2024)
"Land Information Letter" once played an important role in land registration, but their issuance often caused problems such as overlapping and lack of understanding by village heads regarding the legal basis for their issuance. The government continues to strive to improve the land registration system, one of which is by revising Government Regulation Number 24 of 1997 to Government Regulation Number 18 of 2021.This research is a Doctrinal/normative research that adopts a statutory approach to analyze Land Information Letter. The data used are secondary data in the form of primary legal materials, secondary legal materials, and non-legal materials. Based on an in-depth analysis of the position of the “Land Information Letter” as proof of land ownership in the context of land registration in Indonesia, it can be concluded that the “Land Information Letter” does not provide a strong guarantee of legal certainty regarding land ownership. Government Regulation Number 18 of 2021, which changes the function of the “Land Certificate” to merely instructions in the land registration process, is expected to encourage the public to immediately take care of land registration and obtain stronger land title certificates. However, the implementation of this regulation needs to be carried out carefully and pay attention to the rights of vulnerable communities, as well as ensuring that they get sufficient understanding and information regarding changes in land registration regulations.